Cohesion Analysis in the Short Story of Lukisan Bergetar by S Prasetyo Utomo: Jatut Yoga Prameswari dan Dewi Indah Susanti - Jatut Yoga Prameswari; Dewi Indah Susanti (PT. Lancar Media Komunikasi, 2022)
Literary works in the form of prose fiction presented in the form of narrative text in short written language are referred to as short stories. This short story itself certainly contains both cohesiveness and unity between sentences and between paragraphs and makes the short story interesting to read and research. The focus and purpose of this research is to find and describe the form of cohesion found in the short story of Lukisan Bergetar by S Prasetyo Utomo. This research is a type of qualitative research with the research technique used is contentanalysis. The short story of the Lukisan Bergetar by S Prasetyo Utomo is the main data source in this research. Meanwhile, the number of sentence pairs included in lexical cohesion is 8 pairs of sentences. However, from the sentence pairs that have been analyzed, it is also found that sentence pairs contain mixed cohesion consisting of grammatical cohesion and also lexical cohesion. Keywords: Analysis, Cohesion, Short Story